Leukocyte cell‐derived chemotaxin 2 is a zinc‐binding protein. Issue 5 (22nd January 2013) - Okumura, Akinori; Suzuki, Takehiro; Miyatake, Hideyuki; Okabe, Tomoya; Hashimoto, Yuki; Miyakawa, Takuya; Zheng, Hai; Unoki-Kubota, Hiroyuki; Ohno, Hideaki; Dohmae, Naoshi; Kaburagi, Yasushi; Miyazaki, Yoshitsugu; et al.
Abstract : LECT2 and LECT2 bind by comigration in gel electrophoresis (View interaction: 1, 2, 3) Abstract : ► We show that LECT2 contains a zinc atom by ESI‐MAS and XAFS analyses. ► LECT2 is found to be self‐oligomerized by disulfide bonds in vitro. ► The oligomerization of LECT2 is suppressed by addition of zinc. ► We conclude that zinc contributes to stabilization of the LECT2 structure.